2007
DOI: 10.1080/13501760701314417
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of public education spending in 21 OECD democracies, 1980–2001

Abstract: This paper focuses on the analysis of determinants of public education spending in OECD countries. It starts out by reviewing and replicating the model presented by Castles (1989Castles ( ,1998, finding that only a few of his explanatory variables remain significant in a pooled time-series framework. I present an alternative model that contains socio-economic, political, and institutional variables: the level of economic development, the magnitude of demographic demand, the constitutional veto structure, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
1
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(131 citation statements)
references
References 56 publications
6
111
1
13
Order By: Relevance
“…While some authors found that left-wing parties increase education expenditure (Boix 1998;Busemeyer 2007;Castles 1982Castles , 1989Castles , 1998Hega and Hokenmaier 2002;Iversen and Stephens 2008;Potrafke 2011a;Schmidt , 2007, others reported that right-wing parties tend to spend more on education (Ansell 2008(Ansell , 2010Rauh et al 2011). Adding to the confusion, still others even found no party effects and assigned this to the increasing influence of deindustrialization (Jensen 2011).…”
Section: Introductionmentioning
confidence: 94%
“…While some authors found that left-wing parties increase education expenditure (Boix 1998;Busemeyer 2007;Castles 1982Castles , 1989Castles , 1998Hega and Hokenmaier 2002;Iversen and Stephens 2008;Potrafke 2011a;Schmidt , 2007, others reported that right-wing parties tend to spend more on education (Ansell 2008(Ansell , 2010Rauh et al 2011). Adding to the confusion, still others even found no party effects and assigned this to the increasing influence of deindustrialization (Jensen 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Public education expenditure is related to the level of public social expenditure (Busemeyer, 2007). There is also evidence of a trade-off between state spending for cash-based social welfare programmes and education (Nikolai, 2011).…”
Section: Ratio Of Public Expenditure On Education To Public Social Exmentioning
confidence: 99%
“…B. Cameron und Hofferbert (1974), Castles (1982, 1989) und Verner (1979. Seit Kurzem ist das Interesse an Studien zu Bildungsausgaben, auch aufgrund der sich verbessernden Datenlage, stark angestiegen (Schmidt 2002(Schmidt , 2003a(Schmidt , 2004(Schmidt , 2007Busemeyer 2006aBusemeyer , 2006bBusemeyer , 2007aWolf 2006;Nikolai 2007;Zohlnhöfer 2007;Hokenmaier 2002;Hega/ Hokenmaier 2002;Ansell 2006). Die meisten dieser Studien sind y-zentriert, d. h. es geht vor allem um die Identifizierung der statistischen Determinanten der Bildungsausgaben, unter denen die parteipolitische Zusammensetzung der Regierung nur einer von mehreren Faktoren ist.…”
Section: Die Parteipolitische Zusammensetzung Von Regierung Und Bilduunclassified
“…9 Zu Erklärung von Ausgabenunterschieden in der Querschnittsdimension können Parteieneffekte jedoch auch in dieser Periode beitragen (vgl. Schmidt 2007;Busemeyer 2006Busemeyer , 2007a 1980-2002 1980-1992 1993-2002 1993-2002 1980-2002 1993-2002 1980-2002 1980-2002 (1) (2) (3) (4) (5) (6) (7) Education-at-a-Glance-Datenreihe (OECD 2006) verfügbar. Ein Nachzeichnen sich verän-dernder Prioritäten bei den Hochschulausgaben durch den Vergleich von Sub-Perioden ist daher schwer möglich.…”
Section: Ergebnisseunclassified